A Case Series Examining the 1-year Follow-up Outcomes of Myocarditis Associated with COVID-19 Vaccination - Mohammed Thamer Ali; Ammar Chapra; Samah F. A. Mohamed; Abdel Naser Ghareeb; Maryam Al Kuwari; Sabir Abdul Karim; Tahir Hamid; Emad Ahmed Ali Hassan; Awad Al Qahtani; Nidal Asaad; Jassim Al Suwaidi (Heart Views)
Background: COVID-19 messenger RNA (mRNA) vaccine-related myocarditis, though rare, primarily affects young males and often presents its symptoms within the 1st week postvaccination. Aims and Objectives: To assess the long-term outcomes of individuals diagnosed with myocarditis following COVID-19 vaccination. Materials and Methods: We conducted a case series analysis involving 17 patients diagnosed with inflammatory myocarditis. Results: Symptoms in these patients typically appeared 24–96 h after receiving the COVID-19 mRNA vaccine. Fortunately, the prognosis for these patients is generally favorable, characterized by good short-term recovery and minimal long-term consequences. Follow-up cardiac magnetic resonance imaging (CMR) among our patients revealed alongside a preserved ejection fraction, the absence of fibrosis in 7 out of 13 (54%) patients with minimal residual fibrosis in 5 (38%) patients, whereas the remaining one patient demonstrated fibrosis consistent with hypertrophic cardiomyopathy. Conclusion: Despite the seemingly benign nature of COVID-19 mRNA vaccine-related myocarditis thus far, it is crucial to emphasize the necessity of prolonged clinical and CMR follow-up exceeding 1 year. Extended monitoring is essential to gain a deeper understanding of the true nature of this condition and its potential implications. This comprehensive approach will contribute significantly to ensuring the ongoing safety and efficacy of COVID-19 vaccination programs.